OCT-based quantitative predictors of coronary dissection during rotational atherectomy in severe calcified lesions - Zhou, Yu-he; Zhang, Hong-li; Yang, Yang; Wang, Mei-qin; Pan, Jun; Xu, Tian; Meng, Pei-na; Ye, Fei; Wang, Yan-qing (Frontiers in Medicine, 2025)
BackgroundIn the treatment of coronary calcification by rotational atherectomy (ROTA), guidewire bias is often considered to lead to procedure-associated coronary dissections or perforations. However, the actual meaning of guidewire bias is unclear, though it usually refers to the cross-sectional location of the intravascular imaging (IVI) catheter in the coronary artery. This study tentatively explores the quantitative criteria in optical coherence tomography (OCT) imaging of guidewire bias, which may cause ROTA-induced coronary dissection.MethodsA total of 21 patients with severe calcified coronary lesions who underwent ROTA treatment were enrolled in our study. OCT successfully detected these patients pre-ROTA and post-ROTA. All observed coronary segments were analyzed cross-sectionally at every 1-mm interval after manual coregistration of pre-ROTA and post-ROTA OCT images. ROTA-related coronary dissection was the primary endpoint.ResultsA total of 388 OCT cross-sectional images were effectively measured and analyzed to assess the distribution and characteristics of plaque and OCT catheter location pre-ROTA, as well as the presence or absence of coronary dissections post-ROTA after manual coregistration. According to the receiver operating characteristic (ROC) analysis, the distance from the center of OCT catheter to the media at the bias direction (Dcmb) (area under the curve (AUC): 1.000, p < 0.001, 95% confidence intervals (CI): 0.999–1.000) and the touch angle (AUC: 0.988, p < 0.001, 95%CI: 0.968 to 1.000) were strongly correlated with ROTA-related coronary dissection, with the corresponding cutoff values of 0.720 mm and 98.2° respectively.ConclusionDcmb and touch angle detected by OCT are two valuable and convenient independent predictors of ROTA-related coronary intimal dissections caused by guidewire bias.